Synthesis and Photochromism of Quinolines and Benzo[h]quinolines of 1,3-Diazabicyclo[3.1.0]hex-3-ene - Nosrat O. Mahmoodi; Elham Asadollahi; Hamzeh Kiyani; Nahid Naseri (International Journal of Photoenergy)
1,3-Diazabicyclo[3.1.0]hex-3-ene systems represent a very interesting class of organic materials, possessing unique photochromic properties in the solid state. It has been demonstrated that these compounds form deeply colored, fairly stable materials under UV radiation. Here, for the first time we report synthesis of several 1,3-diazabicyclo[3.1.0]hex-3-enes with premade substituted quinoline and benzo[h]quinoline rings.